2008
DOI: 10.1590/s0044-59672008000300022
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Cerqueirellum Py-Daniel, 1983 (Diptera: Simuliidae) and proven new vector of mansonelliasis from the Ituxi River, Amazon basin, Brazil

Abstract: A new species of the genus Cerqueirellum Py-Daniel, 1983 (Diptera: Simuliidae) is described. The adults are similar to the species C. oyapockense (Floch & Abonnenc, 1946) and C. roraimense (Nunes de Mello, 1974), of which the females are similar, and the males present discrete differences. The main differences of this new species to others of the genus Cerqueirellum are the integument of the larva recovered from stout spines and long cephalic trichomes in the pupa. Some females were infected with Mansonella o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This study reports new species occurring in Rondônia: C. pydanielli, E. rorotaense, C. cauchense, C. ulyssesi, and N. exiguua and also fauna with potential for M. ozzardi transmission (C. pydanielli, C. argentiscutum, C. amazonicum) 14,15 . Among these species, C. pydanielli was frequently captured and found to be exerting hematophagic activity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This study reports new species occurring in Rondônia: C. pydanielli, E. rorotaense, C. cauchense, C. ulyssesi, and N. exiguua and also fauna with potential for M. ozzardi transmission (C. pydanielli, C. argentiscutum, C. amazonicum) 14,15 . Among these species, C. pydanielli was frequently captured and found to be exerting hematophagic activity.…”
Section: Discussionmentioning
confidence: 89%
“…In Brazil, only insects of the Simuliidae family transmit M. ozzardi: Cerqueirellum amazonicum, C. argentiscutum and C. oyapockense [12][13][14] and more recently C. pydanielli are potential vectors for mansonelliasis in the State of Amazonas 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, only simuliid vector species have been known to transmit the disease in Brazil and particularly in AM, two other vector species are implicated in the infection, Cerqueirellum amazonicum and Cerqueirellum argentiscutum (Cerqueira 1959, Shelley & Shelley 1976, Shelley et al 1980. Recently, Pessoa et al (2008) have suggested another species, Cerqueirellum pydanielli, as a potential vector of the disease in AM.…”
mentioning
confidence: 99%